Occupational exposure to mercury. What is a safe level? - Moienafshari, R. (College of Family Physicians of Canada, 1999)
QUESTION: One of my pregnant patients, a dental hygienist, uses mercury in her workplace, but appears to have no symptoms of mercury toxicity. She has heard that mercury might affect her fetus. What should I recommend to her? What is a safe level of mercury in the air for pregnant women? ANSWER: Testing for levels of mercury in whole blood and, preferably, urine is useful for confirming exposure. Currently, mercury vapour concentrations greater than 0.01 mg/m3 are considered unsafe. Also, women of childbearing age should avoid contact with mercury salts in the workplace.